KURIKULUM 2013 UNTUK TOTAL QUALITY EDUCATION DI INDONESIA - Hilmi Fauzi (Universitas Islam Nahdlatul Ulama Jepara, 2017)
The issue of improving the quality of education has always been the focusof the various stakeholders in education. One of the objectives is to prepare learning outcomes (LO) that have competitiveness with their competitors. In addition, also to prepare the LO has the power sanding so that it can be in harmony with the era that has entered this disruptive era. The paper is intended to see how the policy relevance of the government to address the problem. The author uses a management approach in reviewing existing data. This paper uses literature review and is reinforced with data from the field. The results of this paper are several facts - including the following alternative facts: the government through the Ministry of Education with the policy of Curriculum 2013 and Kemenristek Dikti through the Presidential Decree on the Indonesian National Qualification Framework (KKNI) began to make efforts to improve education. There is a paradigm shift, previously focused only on cognitive development, or already towards the affective and psychomotor spheres but still very minimal, and unstructured evaluation, is now more systematic to achieve not only the cognitive, but affective, psychomotor sphere by considering multiple intelligence. Based on these facts it can be concluded that there is a match between education and community needs, so that the crisis of moral decadence, the competence of hope can be overcome. On the same side, the 2013 curriculum is nothing but a government instrument to control the quality of education that is oriented towards quality assurance. Finally, the government -designed education is expected to encourage LOs capable of competence, competitiveness and sanding power that is in harmony with the times. Isu perbaikan mutu pendidikan selalu menjadi fokus dari pelbagaipemangku kepentingan dalam pendidikan. Salah satu tujuannya adalahuntuk penyiapan learning outcomes (LO) yang mempunyai daya saingdengan kompetitornya. Selain itu, juga untuk menyiapkan LO mempunyaidaya sanding sehingga dapat selaras dengan zaman yang sudahmemasuki era disruptif ini. Tulisan ditujukan untuk melihat bagaimanarelevansi kebijakan yang diambil pemerintah untuk mengatasipermasalahan tersebut. Penulis menggunakan pendekatan manajemendalam mengulas data yang ada. Tulisan ini menggunakan kajian pustakadan dikuatkan dengan data dari lapangan. Hasil dari tulisan ini adalahbeberapa fakta –termasuk di dalamnya fakta alternatif sebagai berikut:pemerintah melalui Kementerian Pendidikan dengan kebijakan Kurikulum2013 dan Kemenristek Dikti melalui Kepres tentang Kerangka KualifikasiNasional Indonesia (KKNI) mulai melakukan usaha perbaikan pendidikan.Ada pergeseran paradigma, yang sebelumnya hanya terfokus padapengembangan kognitif, atau sudah menuju ranah afektif dan psikomotor namun masih sangat minim, dan evaluasi yang tidak terstruktur, saat ini lebih sistematis untuk mencapai tidak hanya ranah kognitif, namun afektif, psikomotor dengan mempertimbangkan multiple intelegence. Berdasarkan fakta tersebut dapat disimpulkan bahwasannya sudah ada kesesuaian antara pendidikan dengan kebutuhan masyarakat, sehingga krisis dekadensi moral, kompetensi harapannya dapat diatasi. Pada sisi yang sama ;kurikulum 2013 tidak lain sebagai instrumen pemerintah untuk mengkontrol mutu pendidikan yang beorientasi pada jaminan mutu. Terakhir, pendidikan yang didesain pemerintah diharapkan mampu mendorong LO yang mampu mempunyai kompetensi, daya saing dan daya sanding yang selaras dengan zamannya.